IMPORTANCE AND ADVANTAGES OF USING INTERACTIVE METHODS IN THE EDUCATIONAL PROCESS (American Journal of Interdisciplinary Research and Development, 2024)
This article describes interactive methods in teaching subjects, their advantages, effective methods, features, as well as widely used interactive methods in teaching foreign languages in Uzbekistan.